Flower Seeds Biology and Technology - McDonald, Miller B (CABI, 2014)
Floriculture is a small, but significant, component of the global economy. A recent European study (Hannover University, 2003) estimated the worldwide production value of flowers to be around ?60 billion. The North American production totalled about 10% of this amount. The retail floriculture industry has been steadily increasing in size and importance. For example, in the USA, retail sales of flowers have increased from US$4.7 billion in 1980 to US$19 billion in 2002 (Fig. 1.1).